W poszukiwaniu lepszego życia. Ekonomiczne determinanty decyzji o pozostaniu w Polsce ukraińskich migrantów zagranicznych = In search of a better life. Economic determinants of the decision to stay in Poland by Ukrainian foreign migrants - Michalak, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main goal of the study is to identify the determinants of economic migration decisions of Ukrainian immigrants in the context of their possible stay in Poland. Due to the nature of temporary labour migrations, the author considers as particularly important those determinants of migrationdecisions which are related to economic factors, connected with functioning on the labour market. Thus, the considerations are located within the framework of neoclassical economic theories of migration. The purpose of this study is to reconstruct a catalogue of barriers that may constitute a deterrent for subsequent or more permanent migration decisions.
Keywords: migracje zarobkowe; neoklasyczna teoria migracji; socjologia rynku pracy; projekcje migracyjne; ukraińskie migracje do Polski; labour migrations; neoclassical migration theory; sociology of the labour market; migration projections; Ukrainian migrations to Poland